LaQshya- an uphill climb: a review of implementation of LaQshya programme at a tertiary centre in Chennai - M. Mahalakshmi; K. Kanmani; Vidyaa U. Kirubanidhi; S. Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
LaQshya- labour room quality improvement initiative, a National Quality Assurance Programme was launched by the National Health Mission, Government of India in 2017 for improving the quality of services provided at the time of delivery and immediate post-partum period. The programme has been implemented at the Institute of Social Obstetrics, Government Kasturba Gandhi Hospital for women and children from the year 2019. A plethora of changes have been brought about at the legendary institution since then. A retrospective programme review of the changes brought about at the Institute of Social Obstetrics, Government Kasturba Gandhi Hospital for Women and Children in the dimensions described under the LaQshya program i.e.; structural improvement and process improvement and henceforth a comparison of the various outcome as key performance indicators before and after the implementation of the programme. The quality of Institute of Social Obstetrics Government Kasturba Gandhi Hospital started at the bottom with 40%, under the guidance of LaQshya has improved to an astounding 93% making us the proud bearers of the prestigious platinum badge which was evident with the obvious improvement in various outcome indicators. Despite the implementation, LaQshya was an uphill trudge, to break old habits and restrain into new norms and guidelines, the results as mentioned proved to be a beautiful view at the end of the climb. LaQshya is indeed a boon not only to the mothers benefiting from it but also to the service provider as a tool to be a better health care personnel.